2011
DOI: 10.1074/jbc.m110.176826
|View full text |Cite
|
Sign up to set email alerts
|

Human DNA Polymerase β Mutations Allowing Efficient Abasic Site Bypass

Abstract: The DNA of every cell in the human body gets damaged more than 50,000 times a day. The most frequent damages are abasic sites. This kind of damage blocks proceeding DNA synthesis by several DNA polymerases that are involved in DNA replication and repair. The mechanistic basis for the incapability of these DNA polymerases to bypass abasic sites is not clarified. To gain insights into the mechanistic basis, we intended to identify amino acid residues that govern for the pausing of DNA polymerase ␤ when incorpora… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
8

Relationship

6
2

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 58 publications
(27 reference statements)
0
11
0
Order By: Relevance
“…Gieseking et al identified a variant of human DNA polymerase b from a library of more than 10 000 mutants (generated by error-prone PCR) that exhibited superior lesion-bypass ability than the wild-type enzyme. [48] It was found that a mutation that has a pronounced effect was the substitution of a negatively charged glutamic acid with a positively charged lysine. Furthermore, the presence of a large positively charged DNA binding surface has been shown to promote DNA-lesion bypass by human DNA polymerase h, an enzyme that is able to perform translesion synthesis, as well as Sulfolobus solfataricus P2 DNA polymerase IV (Dpo4), an intensively studied translesion polymerase.…”
Section: Discussionmentioning
confidence: 99%
“…Gieseking et al identified a variant of human DNA polymerase b from a library of more than 10 000 mutants (generated by error-prone PCR) that exhibited superior lesion-bypass ability than the wild-type enzyme. [48] It was found that a mutation that has a pronounced effect was the substitution of a negatively charged glutamic acid with a positively charged lysine. Furthermore, the presence of a large positively charged DNA binding surface has been shown to promote DNA-lesion bypass by human DNA polymerase h, an enzyme that is able to perform translesion synthesis, as well as Sulfolobus solfataricus P2 DNA polymerase IV (Dpo4), an intensively studied translesion polymerase.…”
Section: Discussionmentioning
confidence: 99%
“…It was observed that all tested DNA polymerases of eukaryotic, prokaryotic, and archaic origin accept dXTTP and dXATP as building blocks in primer extension reactions, except for KlenTaq DNA polymerase ( Figure 5). In addition to several commonly used DNA polymerases, we tested DNA polymerase mutants with broadened substrate spectra that had been generated either by directed protein evolution or by site-directed mutagenesis (DNA polymerase b 5P20, [31] Therminator DNA polymerase M3, [32] KlenTaq DNA polymerase DM, [33] and Taq DNA polymerase M1 [34] ). Owing to the presence of an altered configuration of the 3'-hydroxyl group of the synthesized deoxyxylose triphosphates, which is required after incorporation for DNA strand elongation, we investigated how many of the xylose nucleotides can be incorporated in a row.…”
Section: Primer Extension Assaysmentioning
confidence: 99%
“…Primer extension studies: Pol η was purchased from EnzyMax, LLC. Pol β was expressed and purified as described 24. PCNA or PCNA–Ub (100 n M ) and DNA polymerase (pol η: 4 n M , pol β: 8 n M ) were mixed and reactions were started by adding the reaction mix containing template/primer (2 n M ), 1× reaction buffer (50 m M Tris‐HCl, 0.25 mg mL −1 BSA, 1 m M DTT), MgCl 2 (5 m M ), and dNTPs (10 μ M ) for pol η, and template/primer (2 n M ), BSA (0.1 mg mL −1 ), 1× reaction buffer (50 m M Tris‐HCl, pH 7.9, 70 m M KCl, 5 % glycerol, 1 m M DTT), MnCl 2 (2 m M ) and dNTPs (15 μ M ) for pol β.…”
Section: Methodsmentioning
confidence: 99%